2009
DOI: 10.1073/pnas.0900874106
|View full text |Cite|
|
Sign up to set email alerts
|

EGF receptor signaling blocks aryl hydrocarbon receptor-mediated transcription and cell differentiation in human epidermal keratinocytes

Abstract: Fig. 4. Opposing effects of TCDD and EGF on differentiation of NHEKs. (A)NHEKs were grown to confluence, and basal medium, or medium with ␣-naphthoflavone (NF, 1 M) was added 24 h before treatment. CEs were isolated after treatment with either 0.1% DMSO or TCDD (10 nM) for 5 days. (B) NHEKs were grown to confluence, and basal medium with or without EGF (10 ng/mL) was added 24 h before treatment. CEs were isolated after treatment with either 0.1% DMSO or TCDD (10 nM) for 5 days. (C) NHEKs were grown to confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 40 publications
2
93
0
Order By: Relevance
“…In the case of the keratinocyte study, chromatin immunoprecipitation assays indicated that EGF supplementation did not disrupt CYP1A1 promoterAhR binding. Instead, EGF supplementation suppressed the recruitment of the coactivating protein p300 to the AhR-XRE complex (Sutter et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the case of the keratinocyte study, chromatin immunoprecipitation assays indicated that EGF supplementation did not disrupt CYP1A1 promoterAhR binding. Instead, EGF supplementation suppressed the recruitment of the coactivating protein p300 to the AhR-XRE complex (Sutter et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, Sutter et al (2009) reported that the addition of EGF to confluent primary human keratinocyte cultures markedly suppressed the induction of CYP1A1 by TCDD, as well as transcription initiated from reporter constructs Cultures were maintained in complete medium, or shifted to deficient medium, and left untreated, or treated with 10 nM TCDD 6 500 nM gefitinib or 500 nM AG1478. Cultures were treated with gefitinib or AG1478 either 1 or 2 hours after the medium shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher production rates of aryl hydrocarbon receptor (AhR) ligands in vitro by M. furfur have been associated with seborrheic dermatitis isolates (108). AhR is found in sebocytes (169), and its function is modified by epidermal growth factor receptor (EGFR) (268,301). The latter probably has a seborrheic distribution, as antibodies or small molecules that block its function cause a folliculocentric eruption with a seborrheic distribution (36), and the interplay of these two receptors was proposed previously (105).…”
Section: Seborrheic Dermatitismentioning
confidence: 99%
“…eratinocytes are not only primary sensors of stressful conditions but also major players of the extremely complex response in the skin conducting an orchestrated recruitment and functions of the immune cells, fibroblasts, and vascular cells involved in the inflammatory responses and wound healing (30,38). Epidermal growth factor receptor (EGFR) located on the cellular membrane of keratinocytes is widely recognized as a key regulator of numerous essential processes underlying skin development, homeostasis, and repair (30,35,38,39).…”
mentioning
confidence: 99%